The Effect of Role-Playing on the Science Learning Outcomes of Fifth-Grade Students at Gunung Tabur Elementary School - Widya Surachman; I Wayan Kertih; I Wayan Widiana (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
This study aims to analyze the effect of the role-playing method on the learning outcomes in Natural and Social Sciences (IPAS) of fifth-grade students at SD Negeri 003 Gunung Tabur. The study employed a quantitative approach using an experimental method through a quasi-experimental design with a Non-Equivalent Control Group Design. The sample consisted of 60 students, comprising 30 students in the experimental class and 30 students in the control class. The experimental group was treated with the application of the role-playing method, while the control group used conventional teaching methods. Research data were obtained through achievement tests administered as pretests and posttests. Data analysis was conducted using descriptive and inferential statistics with a MANCOVA test to examine the effect of the learning method on student achievement. The results indicated a significant difference in average achievement scores between the two groups, with the experimental class achieving an average score of 84.80, while the control class achieved an average of 74.60. The results of the hypothesis test showed a significance value of 0.000 < 0.05 with an effect size of 0.59, which falls into the large category. These findings indicate that the role-playing method has a significant effect on students’ IPAS learning outcomes. Role-playing can enhance students’ active engagement in the learning process through simulations and group interactions, thereby helping students understand learning concepts more deeply and contextually. Therefore, this method can serve as an effective alternative learning strategy for improving science learning outcomes in elementary schools.